ANALISIS STRUKTUR FISIK DAN BATIN ANTOLOGI PUISI TULUS UNTUK ORANG YANG SALAH KARYA BOY CANDRA - Nur Hidayati, Dian; Junadi, Syafi’ (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study aims to describe: (1) the physical and mental structures in the anthology of poetry Sincere For The Wrong People by Boy Candra 2022; (2) the use of physical and mental structures in an anthology of poetry Sincere For The Wrong People by Boy Candra 2022. The researcher used a descriptive qualitative method with a structural approach. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. validity test is done by triangulation. As for the physical and mental structures in the poetry anthology Sincere For The Wrong People by Boy Candra 2022. a. Physical structure (1) Diction (37 words with connotative meaning), (2) Images (23 visual images, 2 auditory images, 9 tactile images, and 1 tasting images), (3) Concrete words (35 words), (4) Figurative language (4 metaphors, 12 personifications, 16 hyperboles), (5) Typography (2 stanzas 5 poems, three stanzas 5 poems). b. Inner structure (1) Theme (overall on the theme of romance), (2) Taste (found 9 kinds of feelings namely: sad, disappointed, disgusted, resigned, anxious, angry, hate, sad, and empty), (3) Tone and Atmosphere (the tone is sad, gloomy, disappointed, while the atmosphere is sad, suffering, sad, and anxious), (4) Mandate (the whole poem has a message with implied meaning).